2005
DOI: 10.1002/ejic.200500461
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Luminescent Properties of Novel Europium(III) Heterocyclic β‐Diketone Complexes with Lewis Bases: Structural Analysis Using the Sparkle/AM1 Model

Abstract: 3+ energy-transfer rates were calculated using a model of intramolecular energy transfer in lanthanide coordination complexes reported in the literature. The room-temperature PL spectra of the europium(III) complexes are com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 34 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…The spectral characteristics of this complex are comparable to other terpyridine complexes reported by T. Nishioka et al [15]. The energy transfer processes in lanthanide complexes occur via absorption of light by the ligand followed by intramolecular energy transfer from the ligand to the central metal ion [23] suggesting an efficient sensitization process between the ligand and the metal ion with the ligand unit acting as an antenna [24]. The cyclic Voltammogram of the complex (1) is depicted in Figure 5.…”
Section: Molecular Modellingsupporting
confidence: 52%
“…The spectral characteristics of this complex are comparable to other terpyridine complexes reported by T. Nishioka et al [15]. The energy transfer processes in lanthanide complexes occur via absorption of light by the ligand followed by intramolecular energy transfer from the ligand to the central metal ion [23] suggesting an efficient sensitization process between the ligand and the metal ion with the ligand unit acting as an antenna [24]. The cyclic Voltammogram of the complex (1) is depicted in Figure 5.…”
Section: Molecular Modellingsupporting
confidence: 52%
“…The decay times of the two luminescence bands averaged 8.59(70.15) ms in the temperature range of 10-300 K. Similarly, for [Dy(ODA)(phen) Á 4H 2 O] + , the decay times of the 481 and 572 nm luminescence are also identical and independent of temperature, with in average value of 7.33(70.40) ms in the whole temperature range. For phencoordinated complexes, the decay times of the sensitized and non-sensitized luminescence of Ln(III) did not differ, since the energy-transfer from triplet state to Ln(III) is relatively very fast, with in a few nanoseconds [21].…”
Section: Article In Pressmentioning
confidence: 98%
“…Recent research on lanthanide complexes has in fact indicated that Sparkle/AM1 coordination polyhedron geometries are comparable to, if not better than geometries obtained from the best contemporary ab-initio full geometry optimization calculations with effective core potentials [4]. Besides, Sparkle/AM1 calculations are hundreds of times faster [2], and have been recently employed for the study of quantum yields of luminescence for some complexes [5]- [9].…”
Section: Introductionmentioning
confidence: 99%